Pengaruh Model Pembelajaran Alternasi Berbantuan Media PhET Simulations Terhadap Self Efficacy dan High Order Thinking Skill (HOTS) Fisika Siswa SMA - Ummi Qonitatin; I Ketut Mahardika (Jurnal Ilmiah Wahana Pendidikan, 2026)
This research aims to examine and describe the effect of the implementation Alternasi model with PhET Simulations on the self efficacy and high order thinking skills of high school students. This research uses a quantitative approach with a true experimental method. The data collection techniques used in this research are tests in the form of questionnaires and post-tests and non-tests in the form of observation sheets. The data analysis techniques used included quantitative analysis, quantitative analysis of self efficacy, and quantitative analysis of students high order thinking skills. The Mann-Whitney U test results showed an Asymp Sig (2-tailed) value of 0.835, indicating no statistically significant effect on students self efficacy. The high order thinking skills of students in the experimental class had an average of 66.63182 and were tested using a t-test, which yielded a Sig. (2-tailed) of 0.000, meaning that there was a significant effect on high order thinking skills.